Rebuilding Babel: A Constitutive Approach to Tongues‐in‐use. (6th October 2016) - Bencherki, Nicolas; Matte, Frédérik; Pelletier, Émilie
Abstract : In this paper, we suggest that the Montreal School (TMS) tradition of organizational communication offers a fruitful analytical framework that allows us to better take into account the way people practically deal with plurilingual situations as they go on with their daily activities and contribute to shaping their organizations. We identify six core features of TMS and show their analytical power in studying plurilingual interactions. TMS, we argue, is conceptually well equipped to reveal the ways in which multiple tongues are dealt with in everyday organizational settings and to uncover the constitutive nature of tongue‐in‐use.